Utility of Rapid Brilliant Cresyl Blue Stain in Routine Fine Needle Aspiration Cytology - Gurung, P; Hirachand , S; Thapa, R; Pradhanang , S; Kafle, N; Acharya, S; Sedhain, M (Journal of Institute of Medicine Nepal, 2017)
Introduction: Rapid on-site evaluation is commonly performed by pathologists to check for cellular adequacy of fine needle aspirate smears to reduce hospital visits of patients and to make preliminary diagnosis. For rapid evaluation, laboratories use Romanowsky stain, Hematoxylin and Eosin stain, supravital stains and ultra-fast Papanicolaou stain. The aim of the study is to evaluate fine needle aspirate smears on-site for sample adequacy using supravital stain Brilliant Cresyl Blue (BCB), to make preliminary cytological diagnosis and to compare with the routine cytological Papanicolaou stain (Pap) and Giemsa stain.Methods: The study was carried out in the Department of Pathology, Kathmandu Medical College Teaching Hospital from 1st December, 2014 to 31st December, 2015. A total of 115 cases referred from OPD for FNAC were included in the study. FNA was performed under aseptic conditions with a 23-guage needle. Samples were collected for routine stains (Papanicolaou and Giemsa stain) and one air-dried slide was stained with Brilliant Cresyl Blue and examined immediately while patient was in waiting room.Results: Of the 115 cases, the age of patients ranged from 15 to 83 years in which male and female ratio was 1.5:1. There were 35 (30.4%) cases of enlarged lymph nodes, 28 (24%) cases of thyroid lesions, 20 (17.3%) cases of breast lesions, 7 (6%) cases of soft tissue lesion, 3 (3%) cases of salivary gland lesions, 1 (1%) case of lung mass, 1 (1%) case of epididymal swelling and others 20 (17.3%) cases. On rapid staining with brilliant cresyl blue, case sample adequacy was 104 (90%). Repeat aspiration was done in 11 (10%) of cases .Upon rapid staining, 92 (80%) of the cases were benign, 19 (17%) cases were malignant, 4 (3%) cases were inconclusive. After observation of papanicolaou and giemsa stains, there were 94 (82%) benign cases and 21 (18%) malignant cases.Conclusion: On-spot Brilliant Cresyl Blue staining is a good stain to check for sample adequacy and to reduce reaspirations. It is as good as the conventional stains in exhibiting cytomorphology of cells.